PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA INTERAKTIF DENGAN POWERPOINT TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 1 AMPEK ANGKEK - Putri, Nadila Yenida (Departemen Matematika, 2024)
A strong understanding of math problem solving skills is essential for students to develop thinking skills in a variety of real-life situations. Lack of student engagement in class made this ability very low in SMPN 1 Ampek Angkek VIII class. A Problem-Based Learning (PBL) approach, which utilizes the interactive features of PowerPoint, was used to address this problem. The purpose of this study is to find out in detail how mathematical problem solving skills improve after using PBL using PowerPoint interactive media. The secondary objective of this study is to compare the effectiveness of traditional learning model with PBL approach using PowerPoint as interactive media. This study used a descriptive posttest-only control group design, which is a form of quasi-experiment. We can reject H0 because the resulting P-value is 0.005, which is less than the significance threshold of 0.005, when we use a real level of 0.05. There is evidence of skill growth using the PBL model assisted by Powerpoint interactive media, and the results show that the PBL class outperformed the standard class.Keywords– Mathematical Problem Solving Ability, Problem Based Learning, Conventional Learning